Normalizing hostility: TikTok netizens and hate speech on Ahmad Sahroni - Muhammad Syafiq; Ariel Abenaya Simarmata; Tulus Maruli Purba; Johan Wilfridus Pane; Hadlinten Josua Tumanggor; Dian Marisha Putri (Journal Albion : Journal of English Literature, Language, and Culture, 2026)
This study examines hate speech in the comment sections of TikTok news accounts discussing Ahmad Sahroni, a prominent Indonesian political figure. As social media increasingly shapes public opinion and political discourse, understanding how hostile language is produced and circulated online has become essential. The objective of this research is to analyze the linguistic, discursive, and ideological features of hate speech using Fairclough’s (1995) Critical Discourse Analysis framework supported by van Dijk’s (2008) socio-cognitive approach. Data were collected from five major TikTok news accounts, with twenty-five top-liked comments selected for analysis. The findings show that hate speech appears through insults, negative labeling, sarcasm, accusations, and mockery, while some comments reinforce broader narratives of public distrust toward political elites. These results highlight how TikTok’s algorithm and user interaction patterns contribute to the visibility and normalization of hostile discourse. The study provides insights that can support digital literacy efforts and inform policy discussions.